2016
DOI: 10.12911/22998993/65092
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ecological Status of Surface Waters in the River Bystrzyca Lublin

Abstract: The quality of surface water in watercourses in the region of Lublin agglomeration was studied in 2012-2014. Biological and chemical indicators of the study for various sampling sites were detected and the resulting values of the indicators were processed statistically. Rivers characterized by small size and the flow and modification of the riverbed. The resulting low values of macrophyte river index and infusorial index pointed to a poor quality of surface waters. Chemical indicators of the quality of surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
3
8
0
Order By: Relevance
“…Babko et al 2016;Pliashechnyk et al 2018, Majerek et al 2019, then there are much fewer works related to the impact of stormwater runoffs.Bioindication was conducted against the background of water quality assessment using chemical indicators such as BOD 5 and COD. In the literature, there is a some of works relating to the assessment of water quality in the Bystrzyca river within the city of LublinGrzywna et al 2016;Gorzel et al 2018]. According to literature reports, the water quality studies in Bystrzyca conducted in 2016 indicated that in the segment below the Zemborzycki Lake, BOD 5 reached the average value of 7.36 mgO 2 /l at coefficient of variation of 10%[Grzywna et al 2016], which is similar to the value obtained in this study.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Babko et al 2016;Pliashechnyk et al 2018, Majerek et al 2019, then there are much fewer works related to the impact of stormwater runoffs.Bioindication was conducted against the background of water quality assessment using chemical indicators such as BOD 5 and COD. In the literature, there is a some of works relating to the assessment of water quality in the Bystrzyca river within the city of LublinGrzywna et al 2016;Gorzel et al 2018]. According to literature reports, the water quality studies in Bystrzyca conducted in 2016 indicated that in the segment below the Zemborzycki Lake, BOD 5 reached the average value of 7.36 mgO 2 /l at coefficient of variation of 10%[Grzywna et al 2016], which is similar to the value obtained in this study.…”
supporting
confidence: 84%
“…In the literature, there is a some of works relating to the assessment of water quality in the Bystrzyca river within the city of LublinGrzywna et al 2016;Gorzel et al 2018]. According to literature reports, the water quality studies in Bystrzyca conducted in 2016 indicated that in the segment below the Zemborzycki Lake, BOD 5 reached the average value of 7.36 mgO 2 /l at coefficient of variation of 10%[Grzywna et al 2016], which is similar to the value obtained in this study. Slightly lower BOD 5 values were observed by Gorzel et al in the study on the Bystrzyca river tributaries, which was conducted in 2003-2004; the mean BOD 5 values reached the level up to 6.1 mg O 2 /l[Gorzel et al 2018].…”
supporting
confidence: 84%
“…The following tributaries have an outlet into the Bystrzyca River: Kosarzewka at 47 km, Kreżniczanka at 40 km, Czerniejówka at 26 km, Czechówka at 25 km, and Ciemięga at 12 km (from the outlet of the Bystrzyca river). From kilometer 18 to 38, the Bystrzyca River flows through the city of Lublin [51,52]. For this reason, the causes of eutrophication of surface water can be: intensive suburbanization, industrial activity, recreation, and agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Pollution of natural waters is a common phenomenon and its main cause is the presence of various substances in water that may come from natural or artificial sources [Policht-Latawiec et al 2014]. Progressive economic development, especially in various branches of industry, has a negative impact on the environment [Grzywna et al 2016]. The surface waters are the most susceptible to pollution [Kalda and Miętus 2016].…”
Section: Introductionmentioning
confidence: 99%